2022
DOI: 10.1177/15588661221077690
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sense of Community and Job Satisfaction Among Campus Recreation Center Employees

Abstract: Research on the experience of campus recreation participants has been studied extensively. However, scholars have paid relatively little attention to employees of campus recreation. This study examined the relationship between Sense of Community (SOC) and job satisfaction of employees in Campus Recreation Center (CRC), and the impact of demographic information, including job classification and tenure, on the levels of their SOC and job satisfaction. Survey data were collected from CRC employees, including stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Many SFD programs face a variety of challenges in recruiting and retaining employees or volunteers, and the job demands can lead to burnout and high levels of stress (Welty Peachey et al, 2014). Other sporting contexts that rely on student volunteers or employees can also face recruitment and retention challenges (Woo et al, 2022). This study demonstrated how using experiential learning and SDT-aligned strategies can enhance the experiences of volunteers in an SFD program and improve program delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Many SFD programs face a variety of challenges in recruiting and retaining employees or volunteers, and the job demands can lead to burnout and high levels of stress (Welty Peachey et al, 2014). Other sporting contexts that rely on student volunteers or employees can also face recruitment and retention challenges (Woo et al, 2022). This study demonstrated how using experiential learning and SDT-aligned strategies can enhance the experiences of volunteers in an SFD program and improve program delivery.…”
Section: Discussionmentioning
confidence: 99%
“…They worked in the stressful work environment related to demotivation (Kampf, 2013), such as having several positions simultaneously and receiving extra training. In addition, the finding showed that interaction between coworkers, which is an important element of job satisfaction in campus recreation employees (Woo et al, 2022), was severely decreased. The pandemic also caused the failure to offer planned programs and suddenly changed the department's structure, negatively influencing employees’ morale and demotivating them (Kampf, 2013), leading to burnout.…”
Section: Discussionmentioning
confidence: 99%
“…The same has been true for college student involvement in recreational sports, as research has found that recreational sports can be a critical facilitator of cross-cultural competency (Burnett, 2021), a sense of belonging (Woo et al, 2022), and leadership development (Burnett, 2021;Hall et al, 2008) for college students. Yet, the bulk of research into college student involvement in recreational sports has been from the perspective of the student participant, not the student employee (Hall et al, 2008;Woo et al, 2022).…”
mentioning
confidence: 95%
“…Research has found that when college students become more involved on-campus with student organizations and on-campus employment, students tend to earn better grades, persist at their institution, and graduate at higher rates than students who are not involved (Astin, 1993;Kuh, 2009). The same has been true for college student involvement in recreational sports, as research has found that recreational sports can be a critical facilitator of cross-cultural competency (Burnett, 2021), a sense of belonging (Woo et al, 2022), and leadership development (Burnett, 2021;Hall et al, 2008) for college students. Yet, the bulk of research into college student involvement in recreational sports has been from the perspective of the student participant, not the student employee (Hall et al, 2008;Woo et al, 2022).…”
mentioning
confidence: 99%